Analisis Reaksi Pasar Terhadap Perubahan Auto Rejection 15% Menjadi Auto Rejection Simetris - Nia Zairotul Ma'rifah; Fitriyah Fitriyah; Maretha Ika Prajawati (Jurnal Ecogen, 2023)
The condition of the global economy is likely to be experiencing fluctuations from the effects of ecological 19, which affect many sectors of one of the capital markets. Capital markets are affected by fluctuating prices, asa result of these events countries are implementing such policies as price limit (auto excess). Bank Indonesia the central bank/bi decided to raise its key rate by 25 basis points to 8.25 percent. At the current substandard auto drops to 7%. to June 5, 2023 to 15%, and now auto symmetrical again. This condition certainly triggers market reactions. Therefore the purpose of this study is to recognize market responses asa result of these changes in policy. The study population is 55 companies registered in the Indonesia stock exchange (bei). For sample retrieval techniques conducted by simple random sampling methods by taking out 5 companies in all sectors in bei. The data analysis that was used was Shapiro wilk's test for the normality of data, and a hypothetical test used wilxocon signed rank because of insufficient data distribution. Test one specimen t-test and test specimen t-test shows no abnormal return differences in previous and previous periods of auto policy change. But there are differences before and after in the variable trade volume.